STRUKTUR DAN DISTRIBUSI PENDAPATAN RUMAHTANGGA PETANI LAHAN SAWAH DI JAWA DAN LUAR JAWA - HANDEWI P.S. RACHMAN; SUPRIYATI - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
This article following aim to study (1) structure earnings of farmer household of rice fieldfarm in five kabupaten in Java and two kabupaten Off Java, (2) the earnings distributionand bearing of with ownership distribution of farm, and (3) formulating policy suggestionto improve earnings of household. Research use primary data result of survey of farmerhousehold in MH 2000 / 01, MK I and of MK II 2001. Research result indicate that (1)agricultural sector still contribute more than 60% of earnings of household farmer of ricefield farm in research area, and paddy farming system have compartment around 21 -38% in Java and 23 - 41% Off Java to totalizing earnings of household, and there istendency more and more wide of rice field farm of land holding high more and morelevel earnings of household, (2) distribution earnings of household in Java and Off Javahave heavy Lameness level (Index of Gini >0,5) where mean Lameness level ofhousehold compared to heavier Java Off Java, and ( 3) entry of sector non-agriculture instructure earnings of household farmer of rice field farm have negative diffraction toearnings distribution which for example because of the lowering of accessing householdto sector is non-agriculture. Implication of finding is important allocation priority ofresource of development for relevant agricultural sector still placed forward. Inagricultural sector strives the make-up of earnings related to scale efficiency dominationof farm of land holding, usage of seed with quality and efficiency marketing and inputoutput. Besides for the reduce of negative diffraction entry of farmer sector to distributionearnings of household in rice field farm area require to be considered to access householdinto the sector through extension of opportunity of job in sector non-agriculture.